TAXATION OF AGRICULTURAL AND FOREST LAND: COMPARATIVE PERSPECTIVE AND PRACTICE IN SERBIA - Vasiljević, Dušan (Economics of Agriculture, 2016)
This paper discusses contradiction between theoretical preferences for using land as an object of taxation and modest revenues collected through property taxes imposed on agricultural and forest land. The paper starts with a summary of specifcities of the land as an object of the property tax; then, classical economists preferences for the wide use of the land tax are confronted with the comparative research fnding numerous examples of exemptions and favorable treatment enjoyed by agricultural and forest land. The second part of the paper builds on a database of average square meter prices of agricultural and forest land determined by local governments for fscal years 2014 and 2015. The quantitative research provides evidences of inconsistency and volatility of land value assessments at signifcantly higher level than we fnd for structures, indicating that key principles of tax equity are undermined, placing disproportionately high burden on certain categories of land owners.